Adolescents’ Experiences in Heterogeneous Theatre Activity Groups: Aspects of Social Inclusion - Mudėnienė, Juventa (Jaunųjų mokslininkų darbai, 2024)
Relationships between adolescents with disabilities and their non-disabled peers are characterised by certain tensions due to low communication experiences, so joint activities in heterogeneous groups can have a unique positive impact on each participant, while at the same time building community and social interactions. As creative and artistic activities encourage the exploration of personal strengths and abilities, engaging in them allows young people to feel like creators rather than people limited by disability. In this way, they discover new, meaningful social roles. It is important to find out what is the impact of activities in a heterogeneous theatre environment on adolescents’ social inclusion? The novelty of this study is in its retrospective approach: the participants, who are now adults, evaluated their experiences from 10–15 years ago and their relevance to their current social life, self-concept and profession. The aim of the study is to reveal the experiences of members of heterogeneous theatre groups in terms of social inclusion. The objectives of the research are: to find out the experiences of participants with disabilities, to reveal the experiences of adolescence of participants without disabilities, to analyse the experiences of participants in terms of social inclusion. The research methodology was a qualitative social research approach. Data was collected through semi-structured interviews. The method of inductive thematic analysis was chosen for data analysis. An analysis of scientific sources was carried out. Summarizing the analysis of the research, it should be noted that the participation in the heterogeneous theatre groups created positive social experiences for all participants, shaped their values, influenced their choice of profession, hobbies and had a positive impact on their quality of life. For adolescents with disabilities, activities in these groups opened up wider social experiences and creative perspectives, influenced greater self-esteem and determination in decision-making when choosing new activities, and opened up the meaningfulness of life. The participants without disabilities developed sensitivity to disability, changed their preconceptions about the abilities of their peers with disabilities, and developed closer social connections with them.
Keywords: adolescents expierences; disability; heterogeneous theatre; social inclusion